Cinmethylin controls multiple herbicide‐resistant Lolium rigidum and its wheat selectivity is P450‐based. Issue 8 (28th February 2020) - Busi, Roberto; Dayan, Franck E; Francis, Ian; Goggin, Danica; Lerchl, Jens; Porri, Aimone; Powles, Stephen B; Sun, Ci; Beckie, Hugh J
Abstract: BACKGROUND: Multiple‐herbicide resistance in Lolium rigidum and other weed species is increasingly exerting pressure on herbicide discovery research for solutions against resistance‐prone weeds. In this study we investigate: (i) the responses of L. rigidum populations and wheat to the new herbicide cinmethylin in comparison with other pre‐emergence herbicides, (ii) the effect of seed burial depths on cinmethylin efficacy and crop selectivity, and (iii) the basis of cinmethylin selectivity in wheat. RESULTS: Cinmethylin at 400 g ha −1 controls herbicide‐susceptible and multiple‐resistant L. rigidum, with a reduction of >85% in plant emergence and 90% in aboveground biomass. Cinmethylin provides effective control of a large number of field populations of L. rigidum with evident resistance to trifluralin. When the wheat seed is buried ≥1 cm below the cinmethylin‐treated soil surface, the emergence of crop seedlings is not different from the untreated control. The organophosphate insecticide phorate synergizes cinmethylin toxicity in wheat, with an LD50 of 682 g ha −1 in the absence of phorate versus 109 g ha −1 in the presence of phorate (84% reduction). The synergistic effect of phorate with cinmethylin on herbicide‐susceptible L. rigidum appears smaller (a 44% reduction in the LD50 of cinmethylin). CONCLUSIONS: Cinmethylin is effective in controlling multiple‐resistant L. rigidum and appears safe for wheat when the seed is separated at depth from the herbicide applied to the soil surface. The basis of this metabolism‐based selectivity is likely regulated by cytochrome P450 monooxygenases. © 2020 Society of Chemical Industry Abstract : Investigating the responses of L. rigidum populations and wheat to the new herbicide cinmethylin in comparison with other pre‐emergence herbicides, the effect of seed burial depths on cinmethylin efficacy and crop selectivity, and the basis of cinmethylin selectivity in wheat. © 2020 Society of Chemical Industry